Hubungan Kepribadian Hardiness dengan Stress Penyusunan Karya Tulis Ilmiah pada Mahasiswa Tingkat Akhir Program Studi Diploma Tiga Keperawatan Universitas Abulyatama - Hendina Ade Miranda; Syukriadi Syukriadi; Mansuriza Mansuriza (Inovasi Kesehatan Global, 2025)
In the final phase of their studies, students often experience intense psychological pressure, especially when writing their final thesis. If this academic stress is not managed optimally, it can cause mental health problems, reduce internal motivation, and lead to despair in the context of education. Hardiness personality is one of the psychological characteristics that is believed to play a crucial role in dealing with such situations. Hardiness encompasses the dimensions of control, commitment, and the ability to see challenges as opportunities, thereby encouraging individuals to persevere in the face of external pressures. This study focuses on the relationship between hardiness personality and the level of stress experienced by final-year students of the Diploma Three Nursing Study Program at Abulyatama University while writing scientific papers. This study used a correlational quantitative approach with a cross-sectional design, involving 63 students selected through proportional random sampling. The Dispositional Resilience Scale (DRS) was used to measure hardiness, while the Student-Life Stress Inventory (SSI) was used to assess stress levels. Data collection took place from April 26 to May 8, 2025. To obtain valid results, data analysis was performed using the Chi-Square test with a significance level of 0.05. The research findings show a significant negative correlation between hardiness personality and stress levels in the process of writing scientific papers (p=0.004; p<0.05). Students who show high levels of hardiness tend to experience lower stress during the preparation of scientific papers, while those with low hardiness are more vulnerable to high academic pressure. Based on these results, it can be concluded that increasing hardiness in students is very important as a strategy for dealing with academic demands, especially in writing scientific papers. Thus, students are expected to be able to strengthen their self-control, commitment to the learning process, and positive perspective towards various challenges.